Health as public service or right in the businessbetween private actors of the Colombian healthsystem - Manrique- Abril, Fred G. (Universidad Pedagógica y Tecnológica de Colombia, 2014)
After twenty years from the implementation of the General System of Social security in Colombia, is attempted, since the conceptual and historical analysis, to determine the ideological support of the healthcare services. We try to focus in a parallel between the social and juridical visions of the concepts of Fundamental Right and Public Service, as well as the implications that they have in the relationships of people with the state, in terms of guarantees and citizen’s protection. We do an approach to the historical moment that caused the promulgation of the Law 100 of 1993, in terms of the functionality and indicators of the National System of Health created from 1975, and a pursuit to the achievements and mistakes of the new system, with the purpose of inviting to think on the real necessities and necessary strategies to consolidate the Social Security’s System in Colombia.